2017
DOI: 10.1590/2317-6431-2017-1851
|View full text |Cite
|
Sign up to set email alerts
|

Influência das consoantes de alta e baixa pressão intraoral sobre a nasalidade e nasalância da fala em pacientes com fissura de palato reparada

Abstract: RESUMO Introdução Na fissura de palato, a realização de um diagnóstico preciso das alterações de fala auxilia o processo de reabilitação, direcionando o tratamento para a disfunção velofaríngea. Objetivo Determinar o estímulo de fala que melhor identifica a hipernasalidade, comparando a nasalidade da fala e a nasalância em estímulos de alta e baixa pressão intraoral, em indivíduos com fissura palatina. Métodos Quarenta e quatro indivíduos com fissura de palato±lábio operada, de ambos os sexos, com idades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(38 reference statements)
1
1
0
1
Order By: Relevance
“…In general, good intra-rater agreement coefficients were also reported in other studies performed in the institution and in the international literature, with speech sample similar to the one used in the present study (11,(20)(21)(22)(23)(24) . Notwithstanding, well defined internal standards, which grant the stability in their assessment, do not seem to be enough to guarantee reliable results among different raters.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In general, good intra-rater agreement coefficients were also reported in other studies performed in the institution and in the international literature, with speech sample similar to the one used in the present study (11,(20)(21)(22)(23)(24) . Notwithstanding, well defined internal standards, which grant the stability in their assessment, do not seem to be enough to guarantee reliable results among different raters.…”
Section: Discussionsupporting
confidence: 88%
“…These results corroborate the literature that also reports reduced inter-raters agreement coefficients in studies that used the ordinal scale, as an assessment method. Studies performed in the Institution showed coefficients that vary from regular to moderate for several speech samples, including spontaneous conversation (10,22,23) , and in the international literature, moderate coefficients of inter-raters agreement were verified (26,27) . According to some authors, this is a worrying data regarding the speech assessment of individuals with cleft, bearing in mind the importance of the speech resonance as clinical decision guiding (28) .…”
Section: Discussionmentioning
confidence: 89%
“…PETERSON-FALZONE; HARDIN-JONES; KARNELL, 2001;DOTEVALL et al, 2002;SOMMERLAD et al, 2002;JOHN et al, 2006;HAVSTAM et al, 2008;VAN DOORN, 2009;BRANDÃO et al, 2011;BRUSTELLO, 2011;FERREIRA, 2011;HORTIS-DZIERZBICKA;RADKOWSKA;FUDALEJ, 2012;ABDEL-AZIZ, 2013;BARBOSA et al, 2013;SCARMAGNANI et al, 2014;PADILHA et al, 2015;PRADO-OLIVEIRA et al, 2015;MEDEIROS;OLIVEIRA et al, 2016;FERLIN;YAMASHITA, 2017 Na literatura de Fonoaudiologia, alguns estudos avaliaram a influência do uso de amostras de referência na avaliação perceptivo-auditiva de aspectos vocais (GERRATT et al, 1993;YIU, 2002YIU, , 2006BAYLOR, 2006;YIU;MOK, 2007;AWAN;LAWSON, 2009;BRINCA et al, 2015) PADILHA et al, 2015;OLIVEIRA et al, 2016), aos aspectos vocais (GERRATT et al, 1993;YIU, 2002YIU, , 2006BAYLOR, 2006;YIU;MOK, 2007;AWAN;LAWSON, 2009;BRINCA et al, 2015)…”
Section: Concordância Intra-grupo Nas Avaliações Sem E Com Acesso àS unclassified